A ratiometric fluorescence probe for detection of hydrogen sulfide in cells. Issue 43 (14th April 2016) - Wang, Bin; Jiang, Na; Sun, Wei; Wang, Qiufen; Zheng, Gengxiu
Abstract : A near-infrared ratiometric fluorescence probe, BOC, was developed for detection of H2 S. The probe features high selectivity and sensitivity. And BOC has the ability to detect H2 S in living cells. Abstract : A near-infrared ratiometric fluorescence probe for detection of H2 S has been designed, synthesized and evaluated. The probe features high selectivity and sensitivity. Confocal microscopy imaging experiments demonstrate that the probe has potential as a powerful tool for the imaging of H2 S in living cells.